2015
DOI: 10.1101/gad.258350.115
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the RNA polymerase III repressor MAF1 confers obesity resistance

Abstract: MAF1 is a global repressor of RNA polymerase III transcription that regulates the expression of highly abundant noncoding RNAs in response to nutrient availability and cellular stress. Thus, MAF1 function is thought to be important for metabolic economy. Here we show that a whole-body knockout of Maf1 in mice confers resistance to diet-induced obesity and nonalcoholic fatty liver disease by reducing food intake and increasing metabolic inefficiency. Energy expenditure in Maf1 −/− mice is increased by several m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
178
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(190 citation statements)
references
References 63 publications
11
178
0
1
Order By: Relevance
“…The tags were then mapped in three sequential steps and categorized as either mature or precursors as previously described (Bonhoure et al 2015). Each tag contribution to the gene score was weighted according to its length, its number of matches on the transcriptome, and the number of times it was sequenced.…”
Section: Resultsmentioning
confidence: 99%
“…The tags were then mapped in three sequential steps and categorized as either mature or precursors as previously described (Bonhoure et al 2015). Each tag contribution to the gene score was weighted according to its length, its number of matches on the transcriptome, and the number of times it was sequenced.…”
Section: Resultsmentioning
confidence: 99%
“…Coming from a totally different angle, a germline mouse model deficient in Maf1, a repressor of RNA polymerase III transcription of highly abundant cellular RNAs (Upadhya et al, 2002), also underscored the importance of NNMT in NAD + homeostasis. Maf1 -/- mice are resistant to obesity due to metabolic inefficiency as a consequence of futile tRNA production, which led to extreme reductions of NNMT levels, boosting NAM salvage to regenerate NAD + (Bonhoure et al, 2015). In combination, these independent studies in widely different mouse models support that NNMT inhibition enhances NAD + -dependent SIRT1 activity and protects mice against obesity and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…In C. elegans , Maf1 levels can also influence TBP expression in addition to canonical RNA pol III targets [16]. In contrast, a whole-body knockout of Maf1 in mice showed no significant changes in the steady state transcript levels of TBP in liver [41]. At the present time we can only speculate about the reasons for the differences in these results.…”
Section: Introductionmentioning
confidence: 99%
“…This finding functionally links Maf1 levels with lipogenesis from excess sugars. Importantly, studies of the Maf1 knockout mouse revealed a significant increase in the levels of newly synthesized palmitate in Maf1(−/−) livers [41], which suggests the negative regulation of de novo lipogenesis by Maf1 is functionally conserved. However, Acc1 and Fasn transcripts were unaltered, and surprisingly the Maf1(−/−) animals were phenotypically lean.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation